Laboratory evaluation of aqueous Neem Seed "Bitters" (NSB) on the different developmental stages of brackish water breeding anopheline mosquitoes with special reference to anopheles (cellia) litoralis king - Yap, Audwin T.
The efficacy of Neem Seed "Bitters" (NSB) on the eggs, 1st-4th instar larvae, and pupae of Anopheles litoralis King (Sucat strain) was evaluated following the WHO guidelines on Insect Development Inhibitors (IDI) testing (with some modifications). The effect of NBS on the eggs is inconclusive, while it has no effects on the pupae. However, it possesses larvicidal properties. The 1st instar larvae were most susceptible (EC50 = 14.15 mg/L). followed by the 2nd instar larvae (EC50 = 16.26 mg/L), 3rd instar larvae (EC50= 32.55 mg/L), while the 4th instar larvae were most resistant (EC50 = 36.14 mg/L). Morphological aberrations such as the presence of numerous larviform pupae (larval-pupal intermediates) were most evident. The emergence of males with incompletely rotated or unrotated terminalia was also observed. NSB was observed not to cause any growth retardation. However, its effect on the prolongation of the developmental period is found to be dose dependent. At high concentrations, e.g. 200 ml/L, NSB was shown to have prolonged the developmental period to as much as 3 times longer. Furthermore, this results in the death and therefore unsuccessful metamorphosis of the mosquito into viable adults, simulating the mode of action of IGRs.